How the Consumption of Green Public Spaces Contributes to Quality of Life: Evidence from Four Asian Cities - Di Giulio, Antonietta (Archīum Ateneo, 2022)
While green public spaces have been studied in relation to biodiversity and climate change, and in relation to health and social inclusion, there is a need to further understand how they relate to a broader understanding of human wellbeing. Evidence suggests that public spaces play an important role with a view to happiness and mental health, but further evidence is needed on how people actually use such spaces and how human needs are met – and how this might compare across different contexts. This necessitates to linking conceptually, empirically and practically the consumption of such spaces, the notion of the good life, and the management of such spaces. Towards this aim, this article explores quality of life in relation to green public spaces in four cities of South and Southeast Asia: Chennai, Metro Manila, Shanghai and Singapore. Based on empirical research in these cities, we engage in a comparative analysis to discuss how and in what way ‘going to the park’ as a form of consumption is a satisfier towards meeting ‘Protected Needs’ (Di Giulio and Defila, 2020) such as to live in a livable environment, to develop as a person or to be part of a community. The analysis shows that the practice ‘going to the park’ is linked to the practice ‘making the park’, leading to a discussion on how public policies can further support quality of life in cities. On a theoretical note, the article contributes to the debate about how to conceptually link human needs and social practices.